2016
DOI: 10.1051/parasite/2016026
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of afoxolaner in a clinical field study in dogs naturally infested withSarcoptes scabiei

Abstract: The acaricidal efficacy of afoxolaner (NexGard®, Merial) was evaluated against Sarcoptes scabiei var. canis in a field efficacy study, when administered orally at a minimum dose of 2.5 mg/kg to dogs naturally infested with the mites. Twenty mixed-breed dogs of either sex (6 males and 14 females), aged over 6 months and weighing 4–18 kg, were studied in this randomised controlled field efficacy trial. Dogs, naturally infested with Sarcoptes scabiei var. canis confirmed by skin scrapings collected prior to alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 18 publications
5
34
0
2
Order By: Relevance
“…In naturally infested dogs (n ϭ 10), Beugnet et al showed that oral AFX dosed at 2.5 mg/kg also achieved a 100% efficacy on the basis of mite counts at D28 and D56 posttreatment. Clinical scores declined to 80% in the AFX-treated dogs versus 50% in the control group (28). The general observations of the present study were strictly comparable to those of our first trial (24) and successfully replicated previous Australian reports (23,32,33) with regard to the development of disease, strengthening the use of this robust experimental model for drug development.…”
Section: Evaluation Of Afoxolaner In a Porcine Scabies Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…In naturally infested dogs (n ϭ 10), Beugnet et al showed that oral AFX dosed at 2.5 mg/kg also achieved a 100% efficacy on the basis of mite counts at D28 and D56 posttreatment. Clinical scores declined to 80% in the AFX-treated dogs versus 50% in the control group (28). The general observations of the present study were strictly comparable to those of our first trial (24) and successfully replicated previous Australian reports (23,32,33) with regard to the development of disease, strengthening the use of this robust experimental model for drug development.…”
Section: Evaluation Of Afoxolaner In a Porcine Scabies Modelsupporting
confidence: 90%
“…In fact, one pig of three was still infested with live mites at the end of the study. Laboratory or field studies looking at the efficacy of AFX (28) or other isoxazolines such as fluralaner or sarolaner (29-31) against S. scabiei…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates that treatment with a single oral dose (at or approaching the minimum recommended dosage of 2.5 mg/kg) of afoxolaner (NexGard® Chewables) resulted in a rapid reduction in ear mite numbers, suggesting that a single oral administration of NexGard is highly effective (> 98%) against O. cynotis infestations in dogs, as assessed 28 days post-administration. This is comparable to efficacy achieved when afoxolaner was tested against other mite species infesting dogs, namely Sarcoptes scabiei (100% efficacy based on mite counts) [12] and Demodex spp., with > 99% efficacy based on mite counts in a well-controlled study [12] and resolution of cases under field conditions [14]. …”
Section: Discussionsupporting
confidence: 52%
“…It is administered at a minimum dose of 2.5 mg/kg, and comparative studies have shown that monthly administrations of afoxolaner provide outstanding protection against fleas and ticks [10, 11]. Afoxolaner has also demonstrated to be highly efficacious against Sarcoptes scabiei [12] and Demodex canis [13, 14]. Based on these observations, the present study was undertaken to assess the efficacy of a single oral administration of afoxolaner (NexGard) against O. cynotis infestations in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Afoxolaner (NexGard ® , Merial; Lyon, France) is an antiparasitic drug in the class of isoxazolines . The mechanism of action of the isoxazolines is inhibition of chloride channels dependent on glutamate and gamma‐aminobutyric acid (GABA) .…”
Section: Introductionmentioning
confidence: 99%